The role of Colony Stimulating Factor 1 Receptor in microglial phenotype and function in vitro and in vivo - Islam, Sadia (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
As the brain ages multiple cellular processes become less efficient leading to a decline in cognitive and other functions, and in many cases giving rise to chronic neurodegenerative conditions such as Alzheimer’s Disease (AD). Microglial cells are brain macrophages that regulate brain development, maintain neuronal networks, and repair damage and are the key immune cell population during neuroinflammation in chronic neurodegeneration. Inflammation is a consistent feature of neurodegenerative diseases but its precise role remains unclear. However, the role of microglia in AD pathogenesis is unclear, with different studies showing either beneficial or damaging outcomes on disease progression. Understanding how microglia are regulated is essential for identifying new ways of treating AD. A critical growth factor that controls microglial function is Colony Stimulating Factor 1 (CSF1). Neurons produce ligands that are known to activate CSF1R signalling in microglia. During neuronal injury and degeneration, these signals change, bringing about altered microglial function. However, the precise mechanisms by which the CSF1R axis elicits this phenotype remains poorly understood and required further investigation. Additional aspects of microglial function, including the ability to phagocytose protein aggregates and how this is affected by activation of CSF1R signalling may also contribute to disease progression. An unexplored aspect of microglial function is autophagy, a pathway that is often associated to phagocytic processes. In this study, the hypothesis that therapeutic modulation of CSF1R signalling may regulate phagocytic and neuroinflammatory phenotypes was addressed both in a microglial cell line and in the APP/PS1 mouse model of AD. The findings presented in this thesis demonstrate that CSF1 modestly impairs phagocytosis in IMG cells and that inhibition of the CSF1R with GW2580 in vitro may restore normal phagocytosis. The mechanisms of latex bead phagocytosis in IMG cells were not dependent on LC3B-Associated Phagocytosis (LAP). Moreover, despite mTORC1 activation by CSF1R signalling, and mTORC1 inhibition by rapamycin, these treatments had no effect on microglial autophagy, indicating that autophagy is non-canonically regulated (independent of CSF1R and mTORC1 signalling) in IMG cells. In vitro, CSF1R inhibition in the presence or absence of LPS, a model of acute inflammatory stimulation of toll-like receptor (TLR) signalling, influenced several aspects of microglial function including inhibition of LPS-induced CCL2 and CXCL1 and nitric oxide (NO) secretion. In vivo, chronic inhibition of CSF1R signalling by GW2580 in the APP/PS1 mouse model of AD was effective at improving cognitive function in APP/PS1 mice. Molecular analysis of microglial populations from isolated from APP/PS1 and WT mice also provided evidence that microglia display Disease-Associated Microglia (DAM)/ Microglial Neurodegenerative Phenotype (MGnD) phenotypes that were ameliorated by GW2580 treatment of APP/PS1 mice. During the study, it was observed that female mice had more pronounced microglial proliferation. However, GW2580 was more effective in relieving DAM phenotype in male APP/PS1 mice. It was also found that controlling microglial proliferation and phenotype via CSF1R inhibition was sufficient to mitigate synaptic and cognitive signs of disease without any impact on the Aβ levels in the APP/PS1 mouse brain. Taken together, the data presented in this thesis suggest that CSF1R can both inhibit microglial proliferation and alter microglial phenotype and that this may have beneficial outcomes in both acute and chronic neuroinflammatory settings, with possible implications for the treatment of neurodegenerative conditions such as Alzheimer’s disease.
APPROVED